2021
DOI: 10.2147/ijgm.s313486
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Vulnerable Group for Post-Acute Sequelae of SARS-CoV-2 (PASC): People with Autoimmune Diseases Recover More Slowly from COVID-19

Abstract: Purpose: Evidence is emerging that a significant percentage of COVID-19 cases experience symptom persistence beyond 30 days and go on to develop post-acute sequelae. Our objective was to compare the risk for COVID-19 symptom persistence by self-reported use of medications for autoimmune disease among participants of an on-line COVID-19 registry. Patients and Methods: A community-based online survey collected weekly data on COVID-19 symptom presentation. Participants who completed informed consent online, repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
4
10
1
Order By: Relevance
“…We have previously reported that people with autoimmune disorders appeared to be particularly vulnerable to COVID-19, and their response to COVID-19 vaccination may possibly relate to this susceptibility. [11] In contrast, those with diabetes were less likely than others to report vaccine side effects. The lower reporting rates for diabetics may be influenced by an overlap in potential side effects with their metabolic disorder, or they may have found the vaccine associated side effects rather insignificant as a result.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that people with autoimmune disorders appeared to be particularly vulnerable to COVID-19, and their response to COVID-19 vaccination may possibly relate to this susceptibility. [11] In contrast, those with diabetes were less likely than others to report vaccine side effects. The lower reporting rates for diabetics may be influenced by an overlap in potential side effects with their metabolic disorder, or they may have found the vaccine associated side effects rather insignificant as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial heterogeneity across studies was observed in each of the three meta-analyses (I 2 =98.8%, 97.4% and 95.9%, respectively; p<0.001). ASADI-POOYA [24] AUL [91] AYDIN [65] BALDINI [62] FERNÁNDEZ-DE-LAS-PEÑAS [105] SUÁREZ-ROBLES [128] DARCIS [101] DREYER [103] ZAYET [137] YOMOGIDA [34] VENTURELLI [135] VARGHESE [134] TAYLOR [131] TAWFIK [14] SZEKELY [66] SULTANA [129] STAVEM [127] SONNWEBER [58] RIGHI [123] PELUSO [13] O'SULLIVAN [122] O'KEEFE [121] NAIK [54] MOTIEJUNAITE [64] MECHI [44] MALLIA [115] KLEIN [111] GABER [106] EROL [25] DIAZ-FUENTES [102] DANKOWSKI [100] CARFI [96] CORTÉS-TELLES [69] CARVALHO-SCHNEIDER [97] BOARI [94] VIJAYAKUMAR [65] Total (I 2 =95.9%, p<0.001) ZHANG [39] D'CRUZ [35] D'CRUZ [35] TODT [132] TAYLOR [131] SKJORTEN [38] DAYNES [10] APARISI [26] DE GRAAF [61] YIN …”
Section: Prevalence Of Post-covid Breathlessness Among Covid-19 Survi...mentioning
confidence: 99%
“…CARE was launched on April 2, 2020 to study COVID-19 symptoms and severity outside of the hospital setting to examine what factors, if any, mitigate the impact of infection with COVID-19. [20][21][22] The protocol and web technology are updated periodically, with the COVID-19 vaccination questions reported here added on December 15, 2020. Participants are recruited via social media, targeting adult US residents, and are not compensated for participation.…”
Section: Methodsmentioning
confidence: 99%